Prediction of Binding Mode of Secondary Metabolites in Apium graveolens to Bcl-2 - Kee P. Shan; Nyi M. Saptarini; Jutti Levita (Universitas Padjadjaran, 2017)
Developing new cytotoxic agent which has minimal effect against normal cell is required to reduce the side effects obtained from the existing chemotherapy agents. Celery (Apium graveolens) showed several pharmacology activities, including anti-cancer. This study was conducted to predict and visualize the binding mode of ten secondary metabolites in A. graveolens, i.e., apigenin, caffeic acid, kaempferol, limonene, shikimic acid, chlorogenic acid, ascorbic acid, quercetin, eugenol and ferulic acid against Bcl-2. Navitoclax was employed as reference. Molecular dokcing simulation was performed using AutoDoc Vina v.1.5.6. The results showed that the interaction enery (Ei) ranged from -4.20 to -6.01 kcal/mol, whereas inhibition constant (Ki) were 40.15 to 842.29 μM. Kaempferol showed the best affinity to Bcl-2 (Ei=-6.01 kcal/mol; Ki=24,21 μM). Hydrogen bonds were bond between kampferol and Lys20, Ser102, and Arg103, amino acid residues in Bcl-2.In conclusion, Keywords: anti-cancer, Apium graveolens, Bcl-2, navitoclax